(untitled) (Research, Society and Development, 2022)
Objective: To conduct a systematic review of Amoxicillin (AMX) dosing and pharmacokinetics (PK) in obese subjects for the treatment of the outpatient respiratory tract infection which may be a secondary co-infection with COVID-19. Methodology: A systematic review was performed up to January 2022 on MEDLINE, EMBASE, and Web of Science. Full-text manuscripts describing AMX dosing for respiratory infection or PK in obese children, adults, and RYGB bariatric patients treated with AMX were included. Results: A total of 179 records were screened, of which 8 met the inclusion criteria. Four studies described AMX dosing in obese children and adults, while 4 described PK in obese adults and RYGB bariatric subjects. Overall, in the dosing studies, 54% of children >20 kg and 10% <40 kg with respiratory infection were considered underdosed, according to guidelines or recommendations. Underdosing of 10% occurred in both overweight and non-obese children’s groups. For morbidly obese adults, 70% were considered underdosed. In the PK studies, obese and bariatric adult subjects showed reduced exposure compared to normal weight patients for all AMX formulations. Conclusion: More PK studies are needed to confirm the optimal dose of AMX for obese patients, particularly in children. However, considering that all obese and bariatric adults had reduced exposure compared to subjects of normal weight, 1 g 8/8h should be recommended and liquid formulations are preferable for bariatric patients. To minimize the risks of therapeutic failure and avoid toxicity, a higher threshold of doses should be prescribed for obese children.